2004
DOI: 10.1007/s00216-004-2852-2
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS method for the confirmatory determination of aromatic amines and its application in textile analysis

Abstract: A confirmation method for the determination of 18 aromatic amines originating from azo dyes after reductive cleavage was developed. The method is based on the use of high-performance liquid chromatography/tandem mass spectrometry with atmospheric-pressure chemical ionization. For the identification of the analytes one precursor ion and two daughter ions (multi-reaction monitoring, MRM) were selected and the LC-MS/MS parameters optimized to obtain high sensitivity and selectivity. The linear ranges varied from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…Database B contains product ion spectra data and is constructed from the product ion spectra of 3629 compounds obtained from our own research, the Massbank database [23] and literature [24][25][26][27][28][29][30][31]. Of 3629 compounds, the positive ion mode electrospray ionization collision-induced dissociation (CID) MS spectra were converted to binary spectra with a cut-off level at 5 % relative intensity and thus information on ion abundances was removed.…”
Section: Databasesmentioning
confidence: 99%
“…Database B contains product ion spectra data and is constructed from the product ion spectra of 3629 compounds obtained from our own research, the Massbank database [23] and literature [24][25][26][27][28][29][30][31]. Of 3629 compounds, the positive ion mode electrospray ionization collision-induced dissociation (CID) MS spectra were converted to binary spectra with a cut-off level at 5 % relative intensity and thus information on ion abundances was removed.…”
Section: Databasesmentioning
confidence: 99%
“…UHPLC/HRMS-LITMS 2 chromatograms of the separation of twelve phenolic compounds measured in negative ion mode. Accurate mass full scan chromatogram at a resolution of 30 000 (FWHM) at the top, followed by the LITMS 2 of the preselected precursor ions of compounds 1,2,5,8,6,4,11,12,13,9,14 The LOD is not distinguishable from the corresponding lower LOQ for the measured serial dilution.…”
Section: Quantificationmentioning
confidence: 99%
“…Earlier LC/ESI‐MS methods have shown that good separation and detection of aromatic amines and phenols are achievable, at least in simple matrices such as powdered dyes or solid polymers . On the other hand, LC/ESI‐MS can also be applied for the analysis of samples dissolved in hydrophobic matrices as was shown for the determination of degradation products of ester‐based lubricants …”
mentioning
confidence: 99%
“…W dostępnym piśmiennictwie można znaleźć metody oznaczania 3,3'-dimetylobenzydyny w próbkach środowiskowych (woda), płynach ustrojowych człowie-ka (mocz) i w barwnikach [8][9][10].…”
unclassified